Efficiency of Planning, Programming and Delivery of Social Protection Programs on Early Years - Sabbih, Moustafa Amir; Coudouel, Aline; Rahman, Aneeka (World Bank, Washington, DC, 2021)
Investing in children’s human capital is one of the most critical investments a country can make to break the cycle of poverty and reap the demographic dividend. It can support the productivity and competitiveness of the future workforce and thus affect the growth trajectory of the country. Adequate stimulation and nutrition, especially during the first years of life, is critical for children’s physical, cognitive, and socioemotional growth and development. And children who are left behind in their formative years are often unable to reach strong learning outcomes. To maximize the impact of social protection programs, it is critical to: (1) align the allocation of resources with national policies and strategies; (2) design programs that are able to reach their intended beneficiaries with adequate coverage and benefits; (3) ensure efficiency in programming and financing; and (4) ensure efficiency in actual program delivery at the local level. This policy note analyses all four points based on the findings of the recent social protection public expenditure review, but with a particular focus on mother and child programs. It highlights areas where challenges remain and proposes policy recommendations to address those.